Coverage of Quality Maternal and Newborn Healthcare Services in India: Examining Dropouts, Disparity and Determinants - Lucky Singh; Ritam Bubey; Prashant Kumar Singh; Saritha Nair; Rajesh Kumar Rai; M. Vishnu Vardhana Rao; Shalini Singh (Ubiquity Press, 2022)
Background: Abundant research studies has recorded availability, accessibility and quality of antenatal care and safe delivery in India but comparatively less information is known for postnatal care and furthermore limited attempts at capturing the whole spectrum of obstetric and newborn health services. Assessing discontinuity in maternal and child health service utilization provides us holistic information about existing health inequities and barriers in service provision. Objective: Current study evaluated the coverage of quality antenatal care (QANC), delivery care (QDC) and postnatal care (QPNC) in India as a part of a single continuum accounting for significant regional and sub-regional disparities. Methods: This study analyzed nationally representative data obtained from NFHS-4 (2015-16). Included in the data, were 190 898 Indian women who had a recent birth in last five years. Coverage of QANC, QDC and QPNC was examined at the national, state and district level. Bivariate association of key sociodemographic variables with coverage of services was assessed during chi-squared analysis. Multilevel logistic regression analysis examined correlates associated with coverage of services. The output was presented using odds ratios (OR) with 95% CI. Findings: About 23.5% women utilized QANC out of which 92.9% opted for QDC and 35.1% of newborns received QPNC. About 400 and 471 districts out of 640 had less than 30% coverage of QANC and QPNC, respectively. Women residing in rural regions of Bihar and Northeastern states were found with less than 10% coverage of QANC. Regression analysis shows that women with more than 12 years of education and belonging to richest households had increased odds of availing QANC (OR 1.95; 95%CI: 1.84-2.06) and QDC (OR: 2.86; 95%CI: 2.27-3.60), respectively. Conclusion: Focused interventions targeting the delivery of quality services especially ANC and PNC among newborns are imperative to achieve SDG-3 goals to achieve improvement in maternal and newborn health.